Peningkatan Pemahaman Hak Dasar Anak bagi Orang Tua di Tangerang: Program Kolaborasi dengan KemenPPPA - Helsa; Legita, Fathima Eunike; Setyantoro, Gloria Eirene (Fakultas Psikologi Universitas Pancasila, 2024)
Violence and exploitation of children in Indonesia remain serious issues, as indicated by data from the Online Information System for the Protection of Women and Children (Simfoni PPA), which recorded 15,120 cases of child violence in 2023. Based on that, it is very necessary to fulfill children's basic rights, as stated in the 1989 Convention on the Rights of the Child. This Community Service Program (PkM) is a collaboration between Yayasan Mandiri Kreatif Indonesia (Yamakindo), the Ministry of Women's Empowerment and Child Protection (KemenPPPA), and the Faculty of Psychology at Pelita Harapan University (UPH). The program, themed